Project Censored's state of the free press 2025 : the top censored stories and media analysis of 2023-24 - Huff, Mickey; Voitl, Shealeigh; Roth, Andrew Lee, 1968-; Adley, Mnar; Stevens-Bollen, Anson (Censored Press, 2024)
"State of the Free Press 2025 shows how independent journalism can promote civic engagement and reconnect people who have otherwise lost interest in sensational "news" that distracts and polarizes us. Balancing critical analysis with optimistic vision, the book's diverse contributors champion press freedom and critical media literacy to hold the powerful accountable and promote a more just and inclusive society. State of the Free Press 2025 is a joint production of The Censored Press and Seven Stories Press."--